2002
DOI: 10.1002/j.1939-4640.2002.tb02595.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Fine Morphology of Motile Human Sperm Cells is Associated With IVF‐ICSI Outcome

Abstract: The aim of the present prospective study was to determine whether subtle sperm morphological characteristics affect the outcome of intracytoplasmic sperm injection (ICSI), and if so, to identify those that are relevant. For this purpose, we developed a new method, the motile sperm organelle morphology examination (MSOME). The examination is performed in real time using an inverted light microscope equipped with high-power Nomarski optics enhanced by digital imaging to achieve a magnification up to 6300x. MSOME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
354
3
33

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(399 citation statements)
references
References 29 publications
9
354
3
33
Order By: Relevance
“…Traditionally, semen parameters like sperm count, motility and morphology were considered for assessment of male factor. Of these, sperm morphology is much emphasized recently and is proven to be one of the important predictors in determining the fertilizing capacity of sperm both in vivo and in vitro conditions [23][24][25]. Several clinical studies have demonstrated a clear association between sperm head morphology and improvement in IVF success rate [4,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, semen parameters like sperm count, motility and morphology were considered for assessment of male factor. Of these, sperm morphology is much emphasized recently and is proven to be one of the important predictors in determining the fertilizing capacity of sperm both in vivo and in vitro conditions [23][24][25]. Several clinical studies have demonstrated a clear association between sperm head morphology and improvement in IVF success rate [4,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…After drying, glass slides were imaged using a NanoZoomer 2.0 RS with 40× magnification (Hamamatsu). Based on the generated images, sperm were classified into different morphologies as described previously by Bartoov et al75 …”
Section: Methodsmentioning
confidence: 99%
“…Several publications reported that the IMSI procedure is positively associated with pregnancy rates in couples with previous and repeated implantation failures [6,7,9,34] and in patients with an elevated degree of DNA fragmented spermatozoa [27,48]. Moreover, a recently published meta-analysis showed that the IMSI procedure is associated with improved embryo quality, implantation, pregnancy and miscarriage rates [40].…”
Section: Introductionmentioning
confidence: 99%